Influence of processing parameters on the properties of TiN coatings deposited on tool steels using cathodic arc physical vapour deposition technique - 211479 Mubarak Ali; Esah Hamzah (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Doktor Falsafah (Fakulti Kejuteraan Elektrik)) - Universiti Teknologi Malaysia, 2007